Pengaruh Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) Terhadap Kualitas Laporan Keuangan RSJ Dr. Radjiman Wediodiningrat Lawang - Yasmin Amini; Abdul Wahid Mahsuni; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) began to be used by RSJ Dr. Radjiman Wediodiningrat Lawang in the 2022 fiscal year. The second-year running is now RSJ Dr. Radjiman Wediodiningrat Lawang relies heavily on the application built by the Ministry of Finance. Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) is part of the state budget treasury system (SPAN) as an embodiment of the Integrated Financial Management Information System (FMIS) concept on the budget user work unit side to carry out financial management from the planning stage to financial reporting. In its implementation, there are several troubles but this application greatly facilitates work by producing output according to applicable policies and standards. This study aims to find out and analyze how much Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) which consists of budgeting (X1), budget execution (X2), and financial reporting (X3) influences simultaneously or partially the quality of the financial reports (Y) of RSJ Dr. Radjiman Wediodiningrat Lawang. This research is a quantitative study by taking samples from a population and using questionnaire as a primary data collection tool and using multiple regression as a method of data analysis.Keywords: Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI), budgeting, budget execution, financial reporting, quality of the financial reports.